SYSTEMATIC REVIEW OF THE INFLUENCE OF DIGITAL MARKETING, PRODUCT INNOVATION, AND CUSTOMER ENGAGEMENT ON REPURCHASE INTENTION THROUGH BRAND TRUST - Oktaviani Putri Dita; Budi Eko Soetjipto; Ludi Wisnu Wardhana (RADJA PUBLIKA, 2025)
The digital technology transformation has revolutionized marketing practices, with digital marketing, product innovation, and customer engagement emerging as key determinants in shaping repurchase intention. The mediating role of brand trust in the complex relationships among these variables remains relatively underexplored in the literature. This study aims to examine these relationships through a Systematic Literature Review (SLR) approach, focusing on articles from reputable international journals published between 2019 and 2024. The findings indicate that digital marketing enhances brand awareness, customer experience, and brand trust, all of which collectively contribute to repurchase decisions. Product innovation has been shown to strengthen customer loyalty, though its effectiveness is significantly influenced by the degree of customer involvement in the innovation process. Customer engagement, particularly in digital commerce and social media contexts, plays a central role in driving repurchase intention, with brand trust acting as a mediator that reinforces this relationship. These findings expand the theoretical foundations of the Theory of Planned Behavior (TPB), the Stimulus-Organism-Response (S-O-R) model, and Brand Relationship Theory by emphasizing the importance of the interaction between customer engagement and brand trust in fostering long-term loyalty. From a practical perspective, this study highlights the urgency of adopting data-driven marketing strategies, personalized digital experiences, and innovation that incorporates customer participation. Although limited to secondary data, this research provides relevant contributions to both academia and industry practices. Further studies are recommended to empirically test the causal relationships among variables and assess the influence of demographic and regulatory factors on brand trust formation in the digital marketing era.